2022
DOI: 10.1101/2022.04.13.488268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute appendicitis manifests as two microbiome state types with oral pathogens influencing severity

Abstract: Mounting evidence suggests that acute appendicitis (AA) is not one but two diseases: complicated appendicitis, which is associated with necrosis leading to perforation or periappendicular abscess, and uncomplicated appendicitis, which does not necessarily result in perforation. Even though AA is the most frequent cause of surgery from abdominal pain, little is known about the origins and etiopathogenesis of this disease, much less regarding the different disease types. In this study, we investigated the microb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Second, we only included male patients due to the scarcity of female HUD patients. Third, the analyses in this study predominantly concluded at the genus level due to the limitations of 16S rDNA sequencing in accurately resolving taxa beyond this level (Johnson et al, 2019;Blohs et al, 2023). However, we still propose a strong correlation between HUD and gut dysbiosis.…”
Section: Discussionmentioning
confidence: 69%
“…Second, we only included male patients due to the scarcity of female HUD patients. Third, the analyses in this study predominantly concluded at the genus level due to the limitations of 16S rDNA sequencing in accurately resolving taxa beyond this level (Johnson et al, 2019;Blohs et al, 2023). However, we still propose a strong correlation between HUD and gut dysbiosis.…”
Section: Discussionmentioning
confidence: 69%
“…Within the significant genera, we found opportunistic pathogens such as Parvimonas and Peptostreptococcus were significantly increased in appendicitis ( Figure 5D ). A previous publication also reported increased Parvimonas specific to complicated appendicitis that was associated with oral bacterial pathogens such as Fusobacterium 10 . While increased Fusobacterium has repeatedly been associated with appendicitis in the literature, we observed a trend towards an increase in this genus, although it did not reach significance 7, 22, 23 .…”
Section: Resultsmentioning
confidence: 80%
“…From these studies a few common findings have emerged, including a relative decrease in Bacteroides and increases in oral pathobionts such as Fusobacterium, Gemella and Porphyromonas in appendicitis samples [6][7][8] . The degree of dysbiosis appears to correlate with disease severity, with oral taxa and opportunistic pathogens such as Parvimonas micra more often enriched in complicated appendicitis characterized by gangrenous or perforated tissue, while uncomplicated cases had a lesser dysbiosis composed of typical gut commensal taxa [9][10][11] . Further implicating the microbiome in disease etiology is the result of the APPAC randomized clinical trial, which demonstrated that antibiotic therapy alone can be effective in some cases of appendicitis 12 .…”
Section: Introductionmentioning
confidence: 99%